The American Television Hero as a Novelist of Himself: : Language as Tópos in Matthew Weiner’s Mad Men - Amezcua, David (International Journal of English Studies, 2025)
This article tackles the manifestations of American literary themes in Matthew Weiner’s Mad Men. I contend that the transmedial alignment of TV series and literature heightens our understanding of fundamental myths of American exceptionalism. This paper studies the role of language at script level as a site or tópos where the protagonist’s constant reinvention occurs. Moreover, it provides an interdiscursive analysis of Frank O’Hara’s “Mayakovsky” and John Cheever’s “The Swimmer” to show their thematic connection, which is the transition from old to new life. This theme possesses an axiomatic role in the genesis of this show, suggesting a tight intermedial relationship between the show’s scripts and the two literary works I will analyze. On the basis of my analysis, I suggest that reading this TV series as literature is possible if we consider both the show’s thematic connection with American literary themes and its multiple literary references.